Ardisia japonica (Thunb.) Blume and Lespedeza cuneata G. Don may treat chronic obstructive pulmonary disease by targeting HK2 and PTAFR - Xian Luo; Zheng Hang Ge; Shan Luo; Bo Li; Xun Zhou; Yi Yang; Yong Jiang; Tao Tan; Ke Lin Wang (Frontiers in Medicine)
IntroductionPrevious studies have demonstrated the significant efficacy of Ardisia japonica (Thunb.) Blume (Zijinniu) and Lespedeza cuneata G. Don (Tiesaozhou) in alleviating cough and reducing phlegm. This study employed network pharmacology and bioinformatics approaches to identify key genes associated with Zijinniu and Tiesaozhou in chronic obstructive pulmonary disease (COPD), offering insights into potential therapeutic strategies.MethodsData on COPD, along with the active ingredients and target genes of Zijinniu and Tiesaozhou, were utilized. By integrating the results of differential expression analysis and the target genes of these two plants, candidate genes were identified. Key genes were then confirmed through gene expression analysis in the GSE124180 and GSE42057 datasets. A nomogram was constructed based on these genes to assess COPD risk, followed by validation. Additionally, functional analysis, immune factor profiling, molecular docking, and reverse transcription-polymerase chain reaction (RT-qPCR) were performed.ResultsHK2 and PTAFR emerged as critical genes for COPD treatment, exhibiting significantly elevated expression in COPD samples. RT-qPCR confirmed the significantly higher expression of HK2 (P = 0.0425) in COPD samples. These findings highlight the potential of HK2 and PTAFR as therapeutic targets for COPD. Functional analysis further indicated that HK2 and PTAFR were co-enriched in pathways such as the “chemokine signaling pathway” and “FC gamma R-mediated phagocytosis,” suggesting their involvement in immune responses. Immune factor analysis revealed strong correlations between these genes and various chemotactic factors (e.g., CCL23, CCL5), immunosuppressants (e.g., IDO1, CSF1R), immunostimulants (e.g., ICOS, CD28), chemokine receptors (e.g., CXCR1, CXCR2), and major histocompatibility complex (MHC) molecules (e.g., HLA-B). Molecular docking revealed favorable binding energies between HK2 and quercetin (−8.2 kcal/mol), and between PTAFR and daucosterol (−8.4 kcal/mol), suggesting their potential as effective compounds targeting key genes for COPD therapy.ConclusionHK2 and PTAFR were identified as crucial genes in COPD, providing a solid theoretical foundation for future treatment strategies.